2020
DOI: 10.1183/23120541.00070-2020
|View full text |Cite
|
Sign up to set email alerts
|

Lung function changes over 8 years and testosterone markers in both sexes: UK Biobank

Abstract: Higher levels of testosterone have been associated with better lung function in cross-sectional population-based studies. The role of testosterone in lung function in women and in lung function decline in men or women is unclear.We studied 5114 men and 5467 women in the UK Biobank with high-quality spirometry at baseline (2006–2010) and 8.4 years later. We studied cross-sectional associations of total testosterone (TT), calculated free testosterone (cFT), free androgen index (FAI) and sex hormone-binding globu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
(52 reference statements)
3
8
0
Order By: Relevance
“…26 In addition, a recent large study using UK biobank data showed that the effects of testosterone markers on FEV1 decline over the 8 year follow-up were small in both women (mean age; 53.5) and men (mean age; 55.3). 27 The differential effects of sex hormone on lung function decline need to be further evaluated. Taken together, these findings and our observations suggest that the associations between body composition changes and FEV1 decline are more prominent in men than in women, particularly in middle-aged healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…26 In addition, a recent large study using UK biobank data showed that the effects of testosterone markers on FEV1 decline over the 8 year follow-up were small in both women (mean age; 53.5) and men (mean age; 55.3). 27 The differential effects of sex hormone on lung function decline need to be further evaluated. Taken together, these findings and our observations suggest that the associations between body composition changes and FEV1 decline are more prominent in men than in women, particularly in middle-aged healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…[53] found that early menopause was associated with a significantly lower risk of airflow obstruction. Meanwhile, an analysis of the role of testosterone levels and lung function also utilising UK biobank found higher FEV 1 levels among individuals with higher testosterone after adjustment for multiple confounders including age, height, body mass index (BMI), smoking and multiple lifestyle factors [54]. A contribution of the X chromosome to COPD susceptibility is suggested by an increased risk of early onset COPD in females who smoke and also have a mother with COPD.…”
Section: Copdmentioning
confidence: 99%
“…In mice, testosterone treatment restored asthmatic lung exacerbation by attenuating airway inflammation 45 . Population-based studies further supported this concept by showing strong associations between testosterone levels and lung function in men 46 . Although future studies are required to understand these androgen and/or estrogen controlled transcription pathways in improved long-term lung health, these data further support the concept that balanced sex hormone levels are critical for lung health.…”
Section: Discussionmentioning
confidence: 77%
“…Testosterone is produced in the gonads of boys at the age of 10-12 years, peaking in adulthood and declining slowly with increasing age. Agedependent testosterone deficiency may pose another risk factor for reduced lung health 46 .…”
Section: Discussionmentioning
confidence: 99%